Synthesis and characterization of magnetic graphene oxide for arsenic removal from aqueous solution - Sherlala, A.I.A.; Abdul Raman, Abdul Aziz; Bello, Mustapha Mohammed (Taylor & Francis, 2019)
A magnetic graphene oxide (MGO) was developed for the adsorption of As(III) from aqueous solution. The characteristics of MGO were investigated using Fourier-transform infrared (FTIR), X-ray diffraction and field emission scanning electron microscope-E/energy-dispersive X-ray analyses. Batch adsorption experiments were designed using central composite design, and the effects of adsorbent dosage, pH, contact time and concentration of As(III) were investigated. The MGO showed an excellent performance, removing up to 99.95% of As(III) under the following condition: initial As(III) concentration = 100 mg/L, pH = 7, adsorbent dosage = 0.3 g/L and contact time = 77 min. MGO dosage and initial pH were the most significant parameters influencing the process performance. FTIR analysis of the used adsorbent confirms the adsorption of As(III) through complexation between surface functional groups of the MGO and the oxyanions of As(III). The adsorbent maintained a significant level of performance even after four cycles of adsorption. Thus, the developed MGO has the potential to be used for the abatement of arsenic pollution. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.